The rational design and synthesis of novel a-2 andrenoceptor antagonists as potential antidepressants - O'Donovan, Daniel Hillebrand (Trinity College (Dublin, Ireland). School of Chemistry, 2011)
Depression is one of the leading causes of illness worldwide and has been closely linked to low concentrations of monoaminergic neurotransmitters in the brain. Activation of presynaptic alpha-2 adrenoceptors (a2-AR) by the endogenous ligands noradrenaline (NA) and adrenaline (AD) results in a decrease in the release of monoaminergic neurotransmitters. Therefore, the administration of a2-AR antagonists leads to increased concentrations of brain monoamines and constitutes a viable strategy for the treatment for depression.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin.